2016
DOI: 10.14687/ijhs.v13i1.3662
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between turkish junior national judo team athletes’ social values beliefs and self-esteem levels<p>Türk genç milli judo takım sporcularının sosyal değer inançları ile özsaygı seviyeleri arasındaki ilişki

Abstract: The purpose of this study was to investigate the relationship between the self-esteem and the social value size of national youth judo team athletes. Data were collected by Coopersmith Self-Esteem Inventory adapted to Turkish by Özoğlu (1988) and Multidimensional Social Values Scale developed by Yavuz Bolat (2013) with a questionnaire developed by the researchers to gather personal information. Working group of the research consist of Turkish youths (15-19 years old) are struggling in national judo team betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Furthermore, communication and interpersonal relationship skills are an important predictor indicates that this organizational structure is not closed to communication. A study conducted by Baba Kaya et al (2016) found that athletes with FVs, WJVs, RVs, and TVs sizes had higher levels of self-esteem. Therefore, individuals in organizations who develop behavior belonging to PDOC may be said to have a higher level of self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, communication and interpersonal relationship skills are an important predictor indicates that this organizational structure is not closed to communication. A study conducted by Baba Kaya et al (2016) found that athletes with FVs, WJVs, RVs, and TVs sizes had higher levels of self-esteem. Therefore, individuals in organizations who develop behavior belonging to PDOC may be said to have a higher level of self-esteem.…”
Section: Discussionmentioning
confidence: 99%